2017
DOI: 10.3390/en10050692
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Thermal and Dielectric Properties of SrTiO3/Epoxy Nanocomposites

Abstract: SrTiO 3 /epoxy nanocomposites are prepared using the facile solution-processing technique by incorporating SrTiO 3 nanoparticles with different weight fractions into the epoxy resin host. The morphology of the nanoparticles and composites, as well as the thermal conduction characteristics and electrical properties of the composites were investigated via conventional testing methods. The thermal conductivity increased along with the SrTiO 3 weight fractions, and the thermal conductivity of the SrTiO 3 /epoxy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In Equation (9), q˙exp and q˙sim are the experimental and simulation cooling rates, respectively, and C1 and C2 are the WLF equation parameters. Using the conventional value for WLF parameters (C1=17.44 and C2=51.6 normalK), the predicted shift in the T g between experimental measurements (a range of q˙exp = 4.88–6.77 K/s [43]) and our simulation (q˙sim=100×109 normalK/normals) is 72.17–74.63 K, a reasonable agreement between the shifted T g from simulation value range of (410–460 K) and experimental value range of (363–420 K) [43].…”
Section: Resultsmentioning
confidence: 99%
“…In Equation (9), q˙exp and q˙sim are the experimental and simulation cooling rates, respectively, and C1 and C2 are the WLF equation parameters. Using the conventional value for WLF parameters (C1=17.44 and C2=51.6 normalK), the predicted shift in the T g between experimental measurements (a range of q˙exp = 4.88–6.77 K/s [43]) and our simulation (q˙sim=100×109 normalK/normals) is 72.17–74.63 K, a reasonable agreement between the shifted T g from simulation value range of (410–460 K) and experimental value range of (363–420 K) [43].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to the typical empirical expressions adopted for heat transfer, only basic formula building-blocks (i.e., constant, multiplication, division, power) have been considered for the Eureqa fitting. As a result, the simulation results in Table A1 (configurations N. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] have been found to be best fitted (R 2 = 0.99, see Figure 4b) by the following expression:…”
Section: Resultsmentioning
confidence: 99%
“…Carbon fillers such as carbon nanotubes and graphene nanoribbons are often suggested as possible additives in composite materials. In fact, these materials show a remarkable combination of superior thermal [1][2][3][4], electrical [5][6][7], lubrication [8,9] and mechanical [10][11][12] properties, which have the potential to significantly enhance the performance of base materials. In particular, Polymer Nanocomposites (PNCs) with carbon nanofillers are currently employed in a broad variety of industries, such as the energy [13], aerospace [14], biomedical [15], electronics [16,17] and automotive ones [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, cold ones can catch up with them in an easier way, thereby improving the temperature uniformity of the laminate (see Figure 2). From the literature survey, we found that strontium titanate (STO) has temperaturedependent dielectric properties, but its dielectric constant is too high (>150 at 2.45 GHz between 25 °C and 200 °C [22,23]). As a result, STO particles were added into a low dielectric epoxy resin matrix to fabricate our dielectric-variable spacer.…”
Section: Overview Of Our Methodsmentioning
confidence: 99%